Time trend and prevalence analysis of transfusion transmitted infections among blood donors: A retrospective study from 2001 to 2016 - Manisha Shrivastava; Shweta Mishra; Seema Navaid (Wolters Kluwer Medknow Publications, 2023)
Context: Transfusion-transmitted infections (TTIs) remain a major threat to the patients receiving blood. The incidence of the transmission of various infectious agents has reduced ever since the introduction of various molecular techniques for detection. Aims: The study tried to figure out accurate estimates of risk and trend of TTI over a period of sixteen years, essential for monitoring the safety of blood supply and evaluating the efficacy of the currently employed screening procedures. Methods and Material: A total of 57942 blood donors' records were analyzed for the period from January 2001 to December 2016. Chi-square test (χ2) was used to evaluate the relationship between serological positivity and particular donor characteristics. A P value of less than 0.05 was considered statistically significant. Results: Of the 57942 donations, overall prevalence of TTI was 2.7%. Of these, the reactivity rate of hepatitis B (HBV), hepatitis C, HIV, syphilis, and malaria was 1.8%, 0.42%, 0.2%, 0.31%, and 0.017%, respectively with significant P value (P < 0.05, CI: 95%). Overall prevalence was higher in replacement donors as compared to voluntary blood donors. Trend of TTI prevalence decreased from 2001 to 2016. Conclusions: This epidemiological research on TTI is important for the region, as estimated disease burden based on comprehensive epidemiological research provides the foundation for public policy to ensure an easily accessible and adequate supply of safe and quality blood and blood components to the needy patients.